Recurrence/Regrowth in Grade I Meningioma: How to Predict? - Carvalho, Gervásio Teles Cardoso de; Silva-Martins, Warley Carvalho da; Magalhães, Kênia Cristina Soares Fonseca de; Nunes, Cristiana Buzelin; Soares, Aleida Nazareth; Tafuri, Luciene Simões de Assis; Simões, Renata Toscano (Frontiers in Oncology, 2020)
The HLA-G and HLA-E molecules, Ki67, progesterone (PR), estrogen (ER) and androgen receptors (AR), p53, COX-2, and HER2 were studied to assess whether the biological behavior of grade I meningiomas is related to their expression. Tissue samples from 96 patients with grade I intracranial meningiomas were analyzed by immunohistochemistry on tissue microarray blocks (TMA) using antibodies specific for HLA-G, HLA-E, Ki67, PR, ER, AR, p53, COX-2, and HER2. Meningiomas were classified as small (≤ 2 cm, 1.0%), medium (> 2 cm and ≤ 4 cm, 32.3%), and large (> 4 cm, 66.7%). Tumor size was not related to recurrence/regrowth (p=0.486), but was significantly correlated with peritumoral edema (p=0.031) and intratumoral calcifications (p=0.018). Recurrent meningiomas were observed in 14.6% of cases. Immunostaining for each marker was: HLA-G 100%; HLA-E 95.6%; PR 62%; ER 2.1%; AR 6.5%; p53 92.6%; COX-2 100%; HER2 0%; Ki67, mean 2.61±2.29%, median 2.1%. Primary and recurrent meningiomas showed no significant relation with HLA-E and hormone receptors (p>0.05), except for Ki67, where a higher median was observed in recurrent tumors than in primary (p=0.014). The larger the tumor, the more severe the peritumoral edema, and the greater the presence of calcifications. Ki67 appears to be a good biomarker of recurrence/regrowth in grade I meningiomas.